ChemInform Abstract: Synthesis and Characterization of La11+xHg45‐x and RE11Hg44.5 (RE: Nd, Sm) as Hettotypes of the Sm11Cd45 Structure Type. Issue 45 (October 2016) - Tambornino, Frank; Schwaerzer, Kuno; Hoch, Constantin
Abstract: The Hg‐rich amalgams La11, 7 Hg44, 03 (I), Nd11 Hg44.5 (II), and Sm11 Hg44.5 (III) are prepared by dissolving the lanthanoid metals in a Hg surplus (evacuated glass ampoule, 300 °C, 12 h) followed by removal of excess Hg via distillation.